The design of growth and development children's monitoring application: a user-centered approach - Siswati, Tri; ., Nurhidayat; ., Tjaronosari; Widyawati, Herni Endah; Rialihanto, Muhammad Primiaji (International Journal Of Community Medicine And Public Health, 2022)
Background: Due to pandemic COVID-19, intergrated health services post (Posyandu) was disrupted affecting child growth monitoring. A minimum monitoring approach for the health of children is required. The objective of this study was to design a growth and development children's monitoring application. Methods: We applied research and development methods to define and design the app. The Focus Group Discussion (FGD) was conducted to identify user need, including storyboards, content, features, flow, and performance of android application. We also collaborate with technology information expertise to design an app. The research was carried out in Yogyakarta from May to June 2021. Results: The result showed that users needed a comprehensive app based on Android with a minimum data storage space including growth and child development monitoring, considering storyboard design, menu interface, nutritional and developmental children's milestones, interpretation, and recommendation. The growth monitoring interface includes identity, a child’s health history, and anthropometry, while the development monitoring interface contains stimulation and the child’s developmental achievement. We also provide interpretation and recommendations according to children's health. Conclusions: As a conclusion, we indicate that by following the proposed user-centered framework, we successfully design android applications to monitor growth and development in children, namely DEPA 2.1, abbreviation of design and development of anthropometry and development children's applications.